P. Champagne, R. Lenoir. D. Merllié, L. Rinto, Introduction à la pratique sociologique - Παναγιωτόπουλος, Ν. (The Greek Review of Social Research, 1990)
[Δε διατίθεται περίληψη / no abstract available]